2006
DOI: 10.3892/or.16.4.781
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk and polymorphisms in genes involved in metabolism of estrogens (CYP17, HSD17β1, COMT and MnSOD): Possible protective role of MnSOD gene polymorphism Val/Ala and Ala/Ala in women that never breast fed

Abstract: Polymorphisms in genes encoding enzymes involved in estrogen metabolism are held to be candidates for associations with breast disease, since there is evidence that circulating estrogens are associated with breast cancer risk. In this study, we evaluated the frequency of different polymorphisms related with estrogen metabolism [COMT Val158Met, CYP17 (5'UTR, T27C); HSD17ß1 Gly313Ser and MnSOD Val16Ala] in a breast cancer resistant population, the Xavante Indians, and the frequencies were compared with the ones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…First, we validated this methodology towards its application for identification of genetic polymorphisms potentially associated with individual cancer risk. We generated seven different DNA pools with 50 DNA samples from a population previously genotyped for the MTHFR (C677T) polymorphism creating different amounts of each allele (10,20,40, 50, 60, 80, 90% for common allele). The results obtained (data not shown) demonstrated the reproducibility of this methodology when the allelic frequencies between individual and pooled genotyping were compared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we validated this methodology towards its application for identification of genetic polymorphisms potentially associated with individual cancer risk. We generated seven different DNA pools with 50 DNA samples from a population previously genotyped for the MTHFR (C677T) polymorphism creating different amounts of each allele (10,20,40, 50, 60, 80, 90% for common allele). The results obtained (data not shown) demonstrated the reproducibility of this methodology when the allelic frequencies between individual and pooled genotyping were compared.…”
Section: Resultsmentioning
confidence: 99%
“…The studied DNA samples are routinely used in our laboratory for breast cancer association studies, including DNA samples from the Xavante Indian population which is characterized by an absolute absence of breast cancer (20). All DNA samples were extracted from 250 µl of whole blood using a commercially available kit according to the manufacturer's instructions (QIAamp DNA extraction kit; Qiagen, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have postulated that Ala-9Val MnSOD polymorphism and cancer association are influenced by variables, such as food (vegetables and meat), high alcohol consumption, smoking habit, pesticide exposition (1,8,26,27) . Some studies reported possible gene-gene association, such as performed by Cox et al (5) , that described interaction MnSOD and glutathione peroxidase (GPX-1) gene polymorphisms associated with increased risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are usually involved in the metabolism of environmental carcinogens, in the repair of DNA lesions induced by exogenous and endogenous carcinogens, and in the control of the cell cycle. Individual polymorphic forms in those genes have been associated with individual susceptibility to different types of cancer namely in breast and thyroid cancer (Conde et al, 2009;Gaspar et al, 2004;Pabalan et al, 2010;Peng et al, 2011;Silva et al, 2005;Silva et al, 2006b;Silva et al, 2006a;Silva et al, 2009;Silva et al, 2010;Silva et al, 2007). Several enzymes have evolved for the detoxification of xenobiotic compounds, and their gene expression is induced in response to the presence of numerous compounds (e.g., polycyclic aromatic hydrocarbons found in tobacco smoke).…”
Section: Introductionmentioning
confidence: 99%